Legal Liability of Digital Influencers as Commercial Brand Users: Pertanggungjawaban Hukum Influencer Digital sebagai Pengguna Merek Komersial - Abella Aurelia Syifa; Aldlyan Meilani; Aulia Putri Insani; Dhuha Nurhidayah; Yeni A Lumbantoruan; Lia Nuraini (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: The rapid evolution of digital technology has transformed global trade, positioning digital endorsement as a primary marketing strategy in the modern retail industry. Specific Background: Influencers now serve dual roles as both public promoters and commercial brand users, significantly steering consumer trust and purchasing decisions. Knowledge Gap: Despite their influence, there is legal ambiguity regarding the accountability of influencers when providing inaccurate product information, as demonstrated by the Helwa Skincare case. Aims: This study analyzes the legal position of influencers as brand users and identifies their legal liability for disseminating information that harms consumers. Results: Findings confirm that influencers function as commercial partners, bearing legal responsibility for their communications. Liability encompasses civil accountability under Article 1365 of the Indonesian Civil Code, criminal liability pursuant to the Electronic Information and Transaction Law, and administrative compliance. Novelty: This research provides a distinct legal framework categorizing influencers as commercial entities rather than mere consumers when engaged in paid endorsements, necessitating strict adherence to transparency and prudence. Implications: The study emphasizes the critical need for strengthened regulatory oversight and mandatory sponsorship disclosure to enhance consumer protection and institutionalize influencer accountability in the digital era. Highlights Influencers acting as commercial partners are legally responsible for the veracity of their promotional content under both civil and criminal statutes. Current legal frameworks require influencers to uphold principles of prudence, honesty, and transparency to mitigate potential consumer harm. Strengthening mandatory sponsorship disclosure is essential to align local regulatory practices with global consumer protection standards. Keywords Digital Endorsement; Influencer Accountability; Consumer Protection; Brand Liability; Legal Liability